COVID-19 an atypical presentation - Baby, Unni R.; Adiody, Supriya; George, Sachin; Thomas, Ronnie; Valsan, Chithra (International Journal of Research in Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) pneumonia usually presents as an unilateral or bilateral lower zone opacities. We wish to highlight a case of COVID 19 presenting as upper lobe consolidation with pre-existing co morbidities and unknown primary source of infection.